Comparing SIMD and MIMD Programming Modes - Ganesan, Ravikanth; Govindarajan, Kannan; Wu, Min-You (Journal of parallel and distributed computing, 1996)
The Connection Machine CM-5 supports both SIMD and MIMD programming modes. The SIMD mode is simulated over the MIMD mode. This simulation is likely to lead to a loss of performance in SIMD programs. This paper describes a comparison of the two programming modes with CM Fortran and message-passing Fortran. Two kinds of benchmarks are discussed. The first kind consists of synthetic benchmarks in which we measure time for basic arithmetic operations and communication time. The second kind consists of application benchmarks. The experimental results conclusively show that message-passing Fortran performs considerably better than CM Fortran. While the CM-5 is obsolete, these issues show up in the T3D and other current machines.